Penatalaksanaan Neuro Senso Dan Terapi Latihan Pada Delay Development Di Griya Fisio Bunda Novy Yogyakarta - Khasanah, Fadlilah, Dwi Rosella Komala Sari, SSt.FT.,M.Fis (2017)
The developmental delay if there is the delay within one the motorist development aspect, speak and social behavior. To know the physiotherapy application on increasing the muscle maintain and functional activity by using modality exercise therapy. Neurosenso and exercise therapy to incres strength and functional activity. After doing therapy 5 times with duration 60 minutes in the first times of therapy, there has been no increase in muscle and functional activity. Incres strenght T0: X - T5: X. While the result of growth delay T0 - T5 there is same at all sector. There has been no creasen in muscle and functional activity, this is due to time constraints in therapy.